Apakah Keputusan Pembelian Produk Indomie Dipengaruhi Oleh Word Of Mouth, Citra Merek Dan Harga - Riski Apriani; Siti Mudurikah; Rayhan Gunaningrat; R. Taufiq Nur Muftiyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purchasing decision process involves consumers in deciding to purchase products/services provided by the company. Factors to consider when making a decision include word of mouth, brand image, product price. The aim of the research is to analyze the influence of word of mouth, brand image and product price on purchasing decisions for Indomie Instant Noodles. The sample size was 100 respondents who were identified as coming from students in the Greater Solo area through distributing questionnaires using random sampling. This research uses IBM SPSS Statistics version 25 for data processing. The research results show that especially word of mouth and price have a positive and significant influence on purchasing decisions. However, the significance value > 0.05 proves that brand image does not have a significant influence on purchasing decisions.